Penerapan fungsi manajemen menurut perspektif islam di organisasi ipnu cabang kabupaten pangandaran - Badriyah, Badriyah; Burhanudin, Burhanudin; Fauzi, Erpan; Kamaludin, Kamaludin; Nurlaelatul, Neneng (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to analyze how the implementation of management functions according to an Islamic perspective in the Nahdlatul Ulama Student Association organization or IPNU Pangandaran District Branch as well as to find out the relevance of the management functions implemented in the IPNU organization with management functions from an Islamic perspective. This study uses a qualitative method, because it is a procedure that produces descriptive data in the form of written or oral data about the implementation of management functions in the IPNU Pangandaran Regency branch of the organization. Also supported by data collection techniques using interviews and deepening of material through literature review. The results of the study on the application of management functions according to an Islamic perspective in the Nahdlatul Ulama Student Association or IPNU Pangandaran Regency Branch made IPNU cadres who were ideological, militant, creative, professional, had civilized managerial and leadership capacities, and had good character.